2015
DOI: 10.1016/j.jmmm.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

First principles calculation of magnetic order in a low-temperature phase of the iron ludwigite

Abstract: a b s t r a c tThe magnetic order of a low-temperature dimerized phase of Fe 3 O 2 BO 3 is investigated through a density functional approach which considers full non-collinear spin-spin interactions, focusing on the 15 K crystalline structure. It is found that Fe spins in the (Fe-Fe) 5 þ dimer, formed during the room temperature structural change of Fe 3 O 2 BO 3 , are parallel and have little freedom to rotate under interaction with neighbor Fe atoms. While the Fe dimer behaves as a heavy single magnetic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(51 reference statements)
2
14
0
1
Order By: Relevance
“…The second type triads ordering corresponds to the experimental data. The magnetic moments ordering in the three leg ladders formed by the first type triads obtained by the authors of is almost the same as with other calculations, moreover in , it is mentioned that Bordet (one of the neutron diffraction studies author) in a private conversation assumed ordering in the triad 4‐2‐4 by type: (↑↑→), but in his published paper the ferromagnetic ordering is proposed. As mentioned above, the irreducible representation τ 5 corresponds to another type of magnetic ordering, which is more consistent with the results of theoretical calculations.…”
Section: Homometallic Ludwigitessupporting
confidence: 83%
See 1 more Smart Citation
“…The second type triads ordering corresponds to the experimental data. The magnetic moments ordering in the three leg ladders formed by the first type triads obtained by the authors of is almost the same as with other calculations, moreover in , it is mentioned that Bordet (one of the neutron diffraction studies author) in a private conversation assumed ordering in the triad 4‐2‐4 by type: (↑↑→), but in his published paper the ferromagnetic ordering is proposed. As mentioned above, the irreducible representation τ 5 corresponds to another type of magnetic ordering, which is more consistent with the results of theoretical calculations.…”
Section: Homometallic Ludwigitessupporting
confidence: 83%
“…In theory, the magnetic ordering in Fe 3 BO 5 was investigated both in individual subsystems: three leg ladders formed by triads 1 and throughout the crystal , the calculation results are only partially consistent with the experimental data. In , it was shown that the magnetic order in Fe 3 BO 5 at 15 K can be described as follows (figure ): the triad of the first type consists of two almost independent elements: the ferromagnetically ordered dimer Fe4a‐Fe2 and weakly bound magnetic moment μ Fe4b . Significant magnetic moment μ Fe4b slant (78°) with regard to the magnetic moments of Fe2‐Fe4a dimer arises from the Fe4b‐Fe3 pairs spin‐spin interactions, which leads in turn to the sample magnetization decrease.…”
Section: Homometallic Ludwigitesmentioning
confidence: 91%
“…The spectroscopic, magnetic, and electronic properties of the oxyborates remain the focus of numerous studies . Special interest is connected with the oxyborates containing transition and the rare‐earth metals.…”
Section: Introductionmentioning
confidence: 99%
“…Both models assume spin orientation in the 424 triad to be parallel to the lattice axis b and orthogonal to that of triad 313; this arrangement was determined from neutron diffraction data [14] and further confirmed by first principles calculations [15] . Formal values of magnetic moments of Co 2+ (S=3/2 ) and Co 3+ (S= 2), were initially assumed.…”
Section: Details Of Calculationmentioning
confidence: 71%
“…3). In the Fe ludwigite, the anti-ferromagnetic low is achieved through canting of one of the Fe4 spin cancels out the uncompensated magnetization of triads 313 [15]. In the cobalt ludwigite demagnetized Co4.…”
Section: Contrary To Fementioning
confidence: 99%